IGSCE Cambridge Biology - Jackie Clegg (Collins IGCSE series, 2006)
International Collins IGCSE Biology has been developed to give maximum support for students studying for the Cambridge International Examinations GCSE. International case studies are used throughout, \'localising\' learning.